CSF pulsations measured in Parkinson’s disease patients using EPI-based fMRI data - Kim, Jun-Hee; Kim, Suhong; Im, Jae-Geun; Chung, Seok Jong; Lee, Phil Hyu; Jeong, Yong; Park, Sung-Hong (Frontiers in Aging Neuroscience, 2024)
Introduction Cerebrospinal fluid (CSF) flow is involved in brain waste clearance and may be impaired in neurodegenerative diseases such as Parkinson’s disease. This study aims to investigate the relationship between the CSF pulsation and the development of dementia in Parkinson’s disease (PD) patients using EPI-based fMRI. Methods We measured CSF pulsation in the 4th ventricle of 17 healthy controls and 35 PD patients using a novel CSF pulsation index termed “CSFpulse” based on echo-planar imaging (EPI)-based fMRI. The PD patients were classified into a PD with dementia high-risk group (PDD-H, n = 19) and a low risk group (PDD-L, n = 16), depending on their development of dementia within 5 years after initial brain imaging. The size of the 4th ventricle was measured using intensity-based thresholding. Results We found that CSF pulsation was significantly higher in PD patients than in healthy controls, and that PD patients with high risk of dementia (PDD-H) had the highest CSF pulsation. We also observed an enlargement of the 4th ventricle in PD patients compared to healthy controls. Conclusion Our results suggest that CSF pulsation may be a potential biomarker for PD progression and cognitive decline, and that EPI-based fMRI can be a useful tool for studying CSF flow and brain function in PD.